Homeschooling, freedom of conscience, and the school as republican sanctuary: an analysis of arguments representing polar conceptions of the secular state and religious neutrality - Oh, Paul (2016)
This paper examines how stances and understandings pertaining to whether home education is civically legitimate within liberal democratic contexts can depend on how one conceives normative roles of the secular state and the religious neutrality that is commonly associated with it. For the purposes of this paper, home education is understood as a manifestation of an educational philosophy ideologically based on a given conception of the good. Two polar conceptions of secularism, republican and liberal-pluralist, are explored. Republican secularists declare that religious expressions do not belong in the public sphere and justify this exclusion by promoting religious neutrality as an end in itself. But liberal-pluralists claim that religious neutrality is only the means to ensure protection of freedom of conscience and religion, which are moral principles. Each conception is associated with its own stance on whether exemptions or accommodations on account of religious beliefs have special legal standing and thereby warranted. The indeterminate nature of religion and allegedly biased exclusion of secular beliefs, cited by some when denying religious exemptions, can be overcome by understanding all religious and conscientious beliefs as having equal standing as conceptions of the good. Analysis of court documents from the Uwe Romeike et al asylum case are guided by these understandings, and relationships among themes are explored. In summary, any stance regarding home education may depend on one’s view of secularism, particularly in relation to whether one views religious neutrality as a means to ensure protection of freedom of conscience or an end in itself.